(3eHGOF GdeMGSHI GdeGdjI (B/s - (3GdOgQGhj, ceGd GdOjf eUWais; (3SdjeGf, eMehO GdSjO s; (3fUQ Gddg, YHOGdhgGHs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2002)
(3GdfXGe GdeMGSHj aj GdefTCJ GdUfGYjI ,GdOaGJQ hGdjhejGJ GdeSGYOI ,JUhjH GdCNWGA ,GdQbGHI GdOGNdjI hYfUQ GdfbOjI , GdeMGSHI Yf GdESJKeGQGJ bUjQI GdCLd , GdeMGSHI Yf GdeOjfjf hChQGb GdbHV , GdeMGSHI Yf GdeNRhf GdSdYj , LQO GdGUhd ZjQ GdfbOjI LQO GdCUhd ZjQ GdedehSI hGdehGQO ,LQO GdEdJRGeGJs
Keywords: (3GdLQOs; (3GdeMGSHI GdJMdjdjIs; (3EeSGc GdOaGJQs